2017
DOI: 10.1051/limn/2017023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water input on plankton temporal dynamics from a managed shallow saline lake

Abstract: La Salada is a shallow saline lake located in the SW of the Pampas subject to significant water management, so the primary objective was to assess whether the water input and physicochemical parameters have an impact on the plankton assemblages over a two year period (2013-dry and 2014-wet). The plankton community structure and physicochemical variables showed substantial changes over the study period. La Salada hosted a plankton community characterized by low diversity and small sized organisms. The nanoplank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…The small cell size and this elongated shape further facilitate their movement among the inorganic sediment particles and their ability to hide in the mud. Small size has also been highlighted in planktic communities (Alfonso, Zunino, & Piccolo, ; Somogyi et al, ) as well as the motile feature (Földi et al, ) in other saline lake ecosystems, where species reduce their cell and pore size due to the osmotic stress (Leterme et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The small cell size and this elongated shape further facilitate their movement among the inorganic sediment particles and their ability to hide in the mud. Small size has also been highlighted in planktic communities (Alfonso, Zunino, & Piccolo, ; Somogyi et al, ) as well as the motile feature (Földi et al, ) in other saline lake ecosystems, where species reduce their cell and pore size due to the osmotic stress (Leterme et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed hydrological cycles (e.g., by water abstraction or resupply) can modify limnological variables (e.g., lower conductivity and pH) (Lengyel et al, ), potentially leading to less extreme features characteristic of fresh water, and therefore resulting in higher diversity. This result calls attention to anthropogenic activities (Alfonso et al, ), including even those undertaken for conservation purposes, which have considerable impacts on biodiversity both on the taxonomic (Heino, ; Stenger‐Kovács et al, ) and at the functional levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the well-known impact of salinity determining community structure, studies have indicated that other physicochemical variables of saline lakes could play a critical role controlling the zooplankton community (Williams, 1998). Other factors, such as habitat permanence, water management, incorporation of freshwater input (enriched by nutrients related to anthropogenic use) and trophic interactions alter the structure of aquatic communities in saline lakes (Alfonso et al, 2017;Echaniz et al, 2009;Larson & Belovsky, 2013;Stenger-Kovács et al, 2014). Zooplankton species richness increases with nutrient enrichment in saline lakes, demonstrating the importance of nutrient supply (Larson & Belovsky, 2013).…”
mentioning
confidence: 99%